2012
DOI: 10.1097/mao.0b013e31826dba83
|View full text |Cite
|
Sign up to set email alerts
|

Oral Steroid Treatment for Hearing Improvement in Ménière’s Disease and Endolymphatic Hydrops

Abstract: The results of this and other studies would indicate that a Ménière's disease or endolymphatic hydrops patient is unlikely to experience an improvement in hearing from a short course of oral steroid. Clinically observed temporary improvement did not sustain over several months. Further work to elucidate the mechanisms underlying hearing loss in hydrops, perhaps focusing on the dendrite damage noted in animal models of hydrops, is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Oral steroids showed an overall improvement in vertigo in one small pilot study, 258 while another cited no hearing improvement with oral steroids. 259 A small prospective cohort study was conducted comparing 2 antiviral treatments in MD (n = 31), and only 39% showed improvement in hearing within 2 months and complete vertigo control (n = 12 of 31). 260 Given the limited amount of high-quality studies looking at the role of these alternative agents as maintenance therapy for chronic MD, this GDG cannot currently make a recommendation on their use.…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…Oral steroids showed an overall improvement in vertigo in one small pilot study, 258 while another cited no hearing improvement with oral steroids. 259 A small prospective cohort study was conducted comparing 2 antiviral treatments in MD (n = 31), and only 39% showed improvement in hearing within 2 months and complete vertigo control (n = 12 of 31). 260 Given the limited amount of high-quality studies looking at the role of these alternative agents as maintenance therapy for chronic MD, this GDG cannot currently make a recommendation on their use.…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…Many therapeutic approaches to Meniere’s disease have been studied. These include a low salt diet and diuretics,8 intratympanic steroid application,9 10 or minimal invasive interventions (such as insertion of a ventilation tube into the tympanic membrane,11 12 endolymphatic sac surgery,13 or pulsed low pressure delivery (using Meniett devices)) 1415 16 17 For patients who do not respond to these treatments, more aggressive procedures can be considered, such as intratympanic application of gentamycin,18 19 plugging of the semicircular canal, labyrinthectomy, or neurectomy 20…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment strategies are directed primarily toward controlling vertigo in these patients given its great impact on daily living. Although hearing does not typically progress to a profound hearing loss, current treatments are largely ineffective against the overall progression of hearing loss in these patients . Furthermore, there appears to be an understanding communicated to the patients, whether through misinterpretation of counseling efforts from those within the field of otolaryngology or gleaned by patients' interpretation of materials that they obtain on their own, that they will progress to deafness with a diagnosis of Meniere's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although hearing does not typically progress to a profound hearing loss, 3 current treatments are largely ineffective against the overall progression of hearing loss in these patients. [4][5][6][7] Furthermore, there appears to be an understanding communicated to the patients, whether through misinterpretation of counseling efforts from those within the field of otolaryngology or gleaned by patients' interpretation of materials that they obtain on their own, that they will progress to deafness with a diagnosis of Meniere's disease. Finally, the fluctuating nature of hearing loss in Meniere's disease impacts the interpretation of hearing improvement in treatment study methodology.…”
Section: Introductionmentioning
confidence: 99%